Amplification of productivity of distillate using cerium oxide nanofluid in solar powered desalination. Issue 1 (31st December 2023) - Kaviti, Ajay Kumar; Akkala, Siva Ram; Ali, Mohd Affan; Anusha, P.; Rajkumar, B.
ABSTRACT: The consumption of clean water has increased directly to population growth. Therefore, several studies are being conducted to enhance clean water production. Solar distillation is one of the ways to enhance the productivity of pure water. The primary objective of this study is to increase the productivity of pure water using nanofluids and to determine the optimal nanofluid concentration. In the present study, cerium oxide (CeO2) is employed as a nanoparticle in the preparation of nanofluids with concentrations of 0.02%, 0.04%, and 0.06%, respectively. In comparison to conventional solar still (CSS), the improved solar still increased its yield by 27.40% on day 1 (D1), 11.91% on day 2 (D2), and 9.70% on day 3 (D3). On three consecutive days, the maximum daily distillate yield was 860 ml, 761 ml, and 735 ml at concentrations of 0.02%, 0.04%, and 0.06%, respectively. Compared to a concentration of 0.06%, the improved solar still with 0.02% nanoparticles generates 17% more distillate. The cost per liter of CSS and MSS was 0.0756 and 0.0634 USD, respectively. The cost per liter of MSS was 19.21% less in contrast to its counterpart CSS. Water quality analysis was also reported due to the nanofluids harmful nature to humanity, and the results were within acceptable limits set by WHO. Further, we compared the results of the current study with the previously reported literature for the benefit of the researchers.